2017
DOI: 10.1080/01621459.2016.1208615
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Local Regression on Manifold-Valued Data

Abstract: We propose an extrinsic regression framework for modeling data with manifold valued responses and Euclidean predictors. Regression with manifold responses has wide applications in shape analysis, neuroscience, medical imaging and many other areas. Our approach embeds the manifold where the responses lie onto a higher dimensional Euclidean space, obtains a local regression estimate in that space, and then projects this estimate back onto the image of the manifold. Outside the regression setting both intrinsic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Sometimes functional data X(t) are observed only at densely spaced time points and observations might be contaminated with measurement errors. In these situations one can presmooth the observations using smoothers that are adapted to a Riemannian manifold (Jupp and Kent 1987;Lin et al 2016), treating the presmoothed curves as fully observed underlying curves.…”
Section: Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes functional data X(t) are observed only at densely spaced time points and observations might be contaminated with measurement errors. In these situations one can presmooth the observations using smoothers that are adapted to a Riemannian manifold (Jupp and Kent 1987;Lin et al 2016), treating the presmoothed curves as fully observed underlying curves.…”
Section: Estimationmentioning
confidence: 99%
“…The intrinsic dimension d is only reflected in the rate constant but not the speed of convergence. Our situation is analogous to that of estimating the mean of Euclidean-valued random functions (Bosq 2000), or more generally, Fréchet regression with Euclidean responses , where the speed of convergence does not depend on the dimension of the Euclidean space, in contrast to common nonparametric regression settings (Lin et al 2016;Lin and Yao 2017). The root-n rate is not improvable in general since it is the optimal rate for mean estimates in the special Euclidean case.…”
Section: Component Analysismentioning
confidence: 99%
“…Regression models for this special case have been well studied (Fisher, Lewis and Embleton 1987;Chang 1989;Prentice 1989;Fisher 1995), including intrinsic models for geodesic regression (Fletcher 2013;Niethammer, Huang and Vialard 2011;Cornea et al 2016), semiparametric regression (Shi et al 2009) and local kernel regression as a generalization of the classical Nadaraya-Watson smoother (Pelletier 2006;Davis et al 2007;Hinkle et al 2012;Yuan et al 2012). Recently, the extrinsic regression model in Lin et al (2015) extends the notion of extrinsic means (see, e.g., Ch. 11 and 18 of Patrangenaru and Ellingson 2015), where extrinsic approaches have been reported to have computational advantages (Bhattacharya et al 2012).…”
mentioning
confidence: 99%
“…In St. Thomas et al (2014), for example, the manifold of the parameters of a statistical model is embedded into a big sphere, while Lin et al (2016) embeds the response manifold of a regression model into a Euclidean space for inference. In section 3.1, a simulation study is carried out to compare the performances of an eGP model with that of an intrinsic one in a regression model with predictors on a sphere.…”
Section: Examplesmentioning
confidence: 99%